AN ANALYSIS OF ILLOCUTIONARY ACTS AND IMPLICATURES IN UNDERSTANDING TOEFL SHORT CONVERSATION - Desi Tri Cahyaningati (Jurnal Sosial Humaniora, 2025)
Listening comprehension is found to be among the most difficult tasks for the learners due to several reasons. Mostly, test-takers find difficulty in interpreting the intended meaning of the utterances in the TOEFL examination. To understand the intended meaning which is implied in and beyond the utterance itself, the test takers must have background knowledge of the context of the utterances. Based on the problems faced by the test takers above, this study gives some solutions in understanding the short conversation in TOEFL so they can draw conclusion of the intended meanings. The writer uses illocutionary acts and implicatures in analyzing the problems found in TOEFL short conversation. Based on the analysis, this study concludes that TOEFL short conversations consist of four illocutionary acts classifications of five. There are Directive, Expressive, Assertive and Commisive. Most of the illocutionary acts found in TOEFL short conversations are directive, assertive and expressive. Meanwhile, Commisive is sometimes found in TOEFL short conversations. This study also gets the data of the implicatures on the utterance in TOEFL short conversations. There are some implicatures that can help the test takers in understanding the intended meaning of the utterance in TOEFL short conversations. Thus to understand the intended meaning on the utterances, the test takers can interpret the meaning by applying the illocutionary act theory and the implicatures. The illocutionary will help the test taker to identify the types of the utterance and then can understand the intended meaning of the utterance. The implicatures will explain what a speaker can imply, suggest, or mean, as different from what the speaker literally says.